Revolutionizing organic synthesis through green chemistry: metal-free, bio-based, and microwave-assisted methods - Banerjee, Sayani; Periyasamy, Sakthi; Muthukumaradoss, Kathiravan; Deivasigamani, Priya; Saravanan, Venkatesan (Frontiers in Chemistry, 2025)
The growing emphasis on sustainable development has propelled green chemistry into a vital framework for designing environmentally benign chemical processes. This review highlights recent advancements in green methodologies for organic synthesis, emphasizing strategies that reduce the use of hazardous reagents and solvents while enhancing efficiency and atom economy. Key approaches include solvent-free reactions; the use of water and ionic liquids as green solvents; biocatalysis employing plant extracts and natural acids; and microwave-assisted synthesis. Notable progress in metal-free oxidative coupling—particularly for synthesizing 2-aminobenzoxazoles, imidazoles, pyrazoles, and Schiff bases—demonstrates the shift away from traditional transition-metal catalysis toward safer alternatives. In addition, innovative transformations using natural catalysts such as pineapple juice and onion peel, microbial biotransformations, and bio-based solvents like eucalyptol and ethyl lactate illustrate the expansive potential of green chemistry. Techniques such as photocatalysis and phase-transfer catalysis further exemplify energy-efficient and selective processes. Collectively, these methods offer high yields, shorter reaction times, and significant environmental benefits. This review underscores the practicality and promise of green chemistry in advancing sustainable organic synthesis, particularly within the pharmaceutical and fine chemical industries.